2020
DOI: 10.1002/bit.27568
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven in silico prediction of regulation heterogeneity and ATP demands of Escherichia coli in large‐scale bioreactors

Abstract: Escherichia coli exposed to industrial-scale heterogeneous mixing conditions respond to external stress by initiating short-term metabolic and long-term strategic transcriptional programs. In native habitats, long-term strategies allow survival in severe stress but are of limited use in large bioreactors, where microenvironmental conditions may change right after said programs are started. Related on/off switching of genes causes additional ATP burden that may reduce the cellular capacity for producing the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Multiple investigations monitored cellular responses upon exposure to industrial conditions, aiming to explain the observed performance losses. Industrial hosts were exposed to substrate heterogeneities, revealing an overflow metabolism [ 22 , 23 ], the disturbance of energy management [ 24 , 25 ] and perturbations of regulatory programs mirrored by metabolomics [ 26 , 27 ], transcriptomics [ 28 , 29 ] and proteomics [ 30 , 31 , 32 ]. Even a population heterogeneity was observed [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple investigations monitored cellular responses upon exposure to industrial conditions, aiming to explain the observed performance losses. Industrial hosts were exposed to substrate heterogeneities, revealing an overflow metabolism [ 22 , 23 ], the disturbance of energy management [ 24 , 25 ] and perturbations of regulatory programs mirrored by metabolomics [ 26 , 27 ], transcriptomics [ 28 , 29 ] and proteomics [ 30 , 31 , 32 ]. Even a population heterogeneity was observed [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, gradients of limiting substrate concentrations, by-products, pH, temperature, and shear rates are formed inevitably. Circulating microorganisms in stirred and gassed large-scale tanks respond to the permanently changing microenvironmental conditions, finally causing uncertainty of process performance, possibly deteriorating key TRY criteria (titer, rate, yield) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Real industrial-scale data, important for validation, are rare. Accordingly, researchers have been employing computational fluid dynamics (CFD) combined with metabolic models with different resolutions to shed light on gradients in the bioreactor that take place at the interface of various physical and biological phenomena [6,[22][23][24][25]. It is worth mentioning that shear gradients may have a significant effect on shear sensitive hosts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations